2016
DOI: 10.1002/ajh.24498
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of opioid use in sickle cell disease

Abstract: Pain, the hallmark complication of sickle cell disease (SCD), is largely managed with opioid analgesics in the United States, but comprehensive data regarding the long-term use of opioids in this patient population is lacking. The pain medication prescription records from a cohort of 203 SCD patients were analyzed. Twenty-five percent were not prescribed opioid medications while 47% took only short-acting opioids, 1% took only long-acting opioids, and 27% took a combination of short-acting and long-acting opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 45 publications
(46 reference statements)
4
30
1
Order By: Relevance
“…Some SCD patients indeed encounter delayed access to legitimate opioid use based on our own clinical experience. Our results showed that there was a cluster of SCD patients (13%) who used more than 50 mg OME daily, despite a relatively low opioid dose usage in the overall SCD patient population (1), which is also consistent with our unpublished observation from the large cohort of commercially-insured SCD patients. This subset of SCD patients may contribute to the misconception that patients with SCD consume more opioids than other chronic pain syndromes, since they tend to be frequent healthcare utilizers.…”
Section: To the Editorsupporting
confidence: 90%
See 1 more Smart Citation
“…Some SCD patients indeed encounter delayed access to legitimate opioid use based on our own clinical experience. Our results showed that there was a cluster of SCD patients (13%) who used more than 50 mg OME daily, despite a relatively low opioid dose usage in the overall SCD patient population (1), which is also consistent with our unpublished observation from the large cohort of commercially-insured SCD patients. This subset of SCD patients may contribute to the misconception that patients with SCD consume more opioids than other chronic pain syndromes, since they tend to be frequent healthcare utilizers.…”
Section: To the Editorsupporting
confidence: 90%
“…We thank Ruan and colleagues for their comments on our recently published study of opioid use in sickle cell disease (SCD)(1), and share their concern that persons with SCD may be unfairly denied needed pain relief during an acute pain crisis. We would like to emphasize that our study addressed daily opioid use as an outpatient rather than need for opioids in the emergency department or during hospitalization for a vaso-occlusive crisis (VOC).…”
Section: To the Editormentioning
confidence: 99%
“…Opioid analgesic medications are the main treatment options for acute and chronic pain caused by SCD, although the literature on the patterns of opioid use in this patient population is rather limited . Most studies were based on a self‐reported questionnaire or diary with relatively small numbers of patients, which may be subject to recall or selection bias .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence on the patterns of opioid use in this patient population is rather limited, and there is still controversy on the dose of opioids that SCD patients use in their daily life . Many believe that patients with SCD tend to use more opioids than many other chronic pain conditions, whereas some studies showed a relatively low opioid dose used in this patient population in their daily life . However, most of the previous studies were based on single institutions with relatively small sample sizes or based on a self‐reported questionnaire or diary, which may limit the generalizability of the results.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation